PENGARUH TINGKAT PELAYANAN, KUALITAS PRODUK DAN KEPERCAYAAN TERHADAP KEPUASAN ANGGOTA MENABUNG DI KOPSYAH-MUI JATIM CABANG BUNGAH - Elinda Kurniawati, Nur; Fithrah Hafiliyah, Diah; Agus Saputra, M. Nasyah; Suwaldiyana, Suwaldiyana (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2025)
Member satisfaction is an important indicator in assessing the performance of Islamic cooperatives. The level of satisfaction can be influenced by several factors, such as service quality, product quality, and the level of member trust in the cooperative. Kopsyah-MUI East Java Bungah Branch, as one of the Islamic cooperatives, strives to increase the loyalty and satisfaction of its members through improving services and providing products that suit their needs. This study aims to determine and analyze the effect of service levels, product quality, and trust on member satisfaction in saving at Kopsyah-MUI East Java Bungah Branch. This study uses a quantitative approach with a field research method. Data were collected through a Likert-scale questionnaire that has been tested for validity and reliability. The population of this study was 3,015 members, and the sampling technique used was probability sampling with the Bungin formula, so that 97 respondents were obtained as research samples. The data analysis technique used multiple linear regression and classical assumption tests. The results of the partial test showed that service quality did not have a significant effect on member satisfaction (sig. 0.666). On the other hand, product quality (sig. 0.000) and trust (sig. 0.050) had a positive and significant effect. Simultaneous test shows that all three variables together have a significant effect on member satisfaction (sig. 0.000). Product quality is the most dominant factor in influencing member satisfaction, followed by trust. Service still needs to be improved, even though it is not statistically significant, because it still plays a role in building positive perceptions.